2015
DOI: 10.1097/brs.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Serum Levels of GFAP, pNF-H, and NSE Compared With Clinical Findings in Severity Assessment of Human Traumatic Spinal Cord Injury

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…[16,17] Previous studies have reported that GFAP can be detected in the serum of SCI patients where it can elicit an immune response. [18] Alternatively, an immune response could have been initiated within the injured spinal cord itself where the blood-spinal cord barrier is disrupted and the concentration of released GFAP/GFAP breakdown products are likely to be substantially higher. Another limitation of the current study is that the consequences of autoantibody production on outcome have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] Previous studies have reported that GFAP can be detected in the serum of SCI patients where it can elicit an immune response. [18] Alternatively, an immune response could have been initiated within the injured spinal cord itself where the blood-spinal cord barrier is disrupted and the concentration of released GFAP/GFAP breakdown products are likely to be substantially higher. Another limitation of the current study is that the consequences of autoantibody production on outcome have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Consistent with this, it has been previously reported that GFAP, as well as other CNS proteins, can be detected in plasma of SCI patients. [51][52][53] Once in the bloodstream, proteins released from the CNS can serve as antigens to trigger a B-cell response and generation of immunoglobulins (i.e., IgGs). Alternatively, the infiltration of immune cells into the damaged cord may allow these cells to contact locally released GFAP, thereby eliciting an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of NSE within CSF in a cohort of 16 SCI patients were increased and correlated with the baseline neurologic impairment being either motor complete (AIS A and B) or motor incomplete (AIS C and D) [18]. Ahadi et al (2015) recently found that also serum NSE levels were significantly higher during the first 48 hours after injury in the 26 traumatic SCI patients included in the study compared to the control group [19]. In a population of 34 patients with vertebral spine fractures, however, the analysis of NSE levels revealed no significant difference [20].…”
Section: Neuron-derived Biomarkersmentioning
confidence: 98%